THE RELATIONSHIP BETWEEN STRESS LEVEL, PICKY EATING BEHAVIOR, AND PHYSICAL ACTIVITY ON BODY MASS INDEX AMONG ADOLESCENT GIRLS - Dyah Ayu Fitriani; Linda Rofiasari; Asri Fitri Yati; Antri Ariani (Universitas Kusuma Husada Surakarta, 2025)
Background: Adolescence is a critical period where energy balance affects nutritional status. An imbalance between energy intake and expenditure during this stage can lead to nutritional disorders, including underweight and overweight conditions. This study aimed to analyze the relationship between stress levels, picky eating behaviour, and physical activity with Body Mass Index (BMI) among adolescent girls.Methods: This quantitative study employed a cross-sectional design involving 106 randomly selected high school female students. Data were collected using standardized questionnaires to assess stress levels (DASS-42), picky eating behaviour (modified CEBQ), and physical activity (PAQ-A), along with direct anthropometric measurements to calculate BMI. Multivariate logistic regression analysis was used.Results: Most respondents were aged 18–21 years (67.9%), with high stress levels (73.5%), picky eating behaviour (83%), and physical inactivity (65.1%). Bivariate analysis found significant associations between stress levels (p = 0.012) and picky eating (p = 0.003) with BMI, where both increased the risk of BMI imbalance. Physical activity showed no significant relationship (p = 0.118). Multivariate analysis confirmed significant associations between stress (OR = 3.13, p = 0.012) and picky eating (OR = 5.42, p = 0.003) with BMI, with physical activity serving as a protective factor (OR = 0.29, p = 0.018).Conclusion: This study concludes that stress levels, picky eating behaviour, and physical activity significantly influence the Body Mass Index (BMI) of adolescent girls. High stress levels and picky eating increase the risk of BMI imbalance, while adequate physical activity serves as a protective factor.